Institutional Critique, An Antology of Artists' Writings. - Alberro, Alexander (The Mitt Press : Cambridge, Massachusetts, 2011)
Stimson, Blake; Rasheed, Aareen; Fraser, Andrea; Laderman Ukeles, Mierle; Guerrilia Girls; Eichhorn, Maria; Rosler, Martha
boek